The whole brain atlas on Cd-Rom [electronic resource] - Johnson, Keith A.; Becker, Alex J. (Boston : Lippincott Williams & Wilkins, 1999)
This atlas is an information resource for brain imaging which integrates clinical information with multimodality imaging data.
Ditempatkan di Koleksi Multimedia, Perpustakaan Perubatan.
CD is available at Koleksi Media, Perpustakaan HUKM
Keywords: Brain -- anatomy & histology -- atlases; Brain Diseases -- diagnosis -- atlases